The Evolution of Skull Base Surgery: A Bibliometric Analysis Spanning Nearly 125 Years - Kurland, David B.; Save, Akshay; Patel, Aneek; Groff, Karenna J.; Snyderman, Carl H.; Pacione, Donato; Golfinos, John G.; Sen, Chandranath (Journal of Neurological Surgery Part B: Skull Base, 2024)
Introduction Skull base surgery has evolved from fundamental elements into a distinct multidisciplinary specialty. Using bibliometrics, we appraised the literature pertaining to skull base surgery since 1900 and studied the emergence of the specialty as a scholarly field.Methods We queried Web of Science for all content from past presidents of the North American Skull Base Society (N = 31) and their self-identified forebears, influences, contemporaries, and trainees (N = 115). Statistical and bibliometric analyses were performed using various Python packages on article metadata.Results Our query returned 28,167 articles. The most pertinent works (N = 15,529), identified algorithmically through an analysis of terms in titles, were published between 1900 and 2024 by 15,286 authors. The field exploded in the latter half of the 20th century, concurrently with increased interdisciplinary and international collaboration, and contemporaneously with the formation of centers of excellence and influential societies. Since 1950, prolific contributors to the field from neurosurgery, otolaryngology, radiology/radiation oncology, plastic surgery, and ophthalmology have increasingly subspecialized in skull base topics. The proportion of female authors in the corpus has grown from <1% in 1980 to 17% in 2023. We identify the articles that comprise the historical roots of modern skull base surgery, map the emergence of fundamental terminology within the corpus, and identify the authors who stand as key nodes of collaboration and influence.Conclusion The field of skull base surgery was born from pioneering individuals with training in varied disciplines. The coalescence of skull base surgery into a distinct and diversified subspecialty has been powered by dedicated collaborative efforts on a global scale.
Keywords: skull base; cranial base surgery; bibliometrics; trends; publications